The Role of Capability, Regulation and the Use of Accounting Information Technology in Financial Management Performance - Leny Suryanty; Mulia Saputra; Syukriy Abdullah (Universitas Syiah Kuala, 2021)
Objective – This study aims to examine the effect of apparatus capability, the complete-ness of regulations, and the use of accounting information technology both simultaneous and partial on the financial management performance in SKPK Aceh Singkil, Indonesia.Design/methodology – The population and unit analysis are the District Work Unit (SKPK) in Aceh Singkil, Indonesia. Respondents comprise of Budget Users (PA-SKPK), SKPK Financial Administration Officials (PPK-SKPK), and Finance Subdivision Heads of 46 SKPK. Documentation technique was utilized and Multiple Linear Regression Analysis was used to test the hypotheses.Results – The results showed that apparatus capability, the completeness of regulations, and the use of accounting information technology simultaneous and partial affected the fi-nancial management performance in SKPK Aceh Singkil. This is a concern for SKPK to pay attention to these variables in improving management performance in Aceh Singkil Regency